Галопом по Европам: повесть / В. Аверин - Аверин Владимир (Черный котенок, 2005)
Экземпляры: (20170428) / Инвентарный номер: 30774 / Цена: 49.90 / Сис.шифр: Р2 / Авт.знак: А19 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6-4